Learning: The role of aesthetics in education (Journal of Science and Technology, 2016)
The study is qualitative and it drew on the historical research method, descriptive and case study methods to examine the link between learning, art, and the creative nature of children. Its aim is totransmit the value of art in enhancing creativity through aesthetics in children and consequently enhance their learning. Thus, the study through the use of document analysis (analyzing the artworks of the children), what the children had to say about their works, interviews and the observation tools throws light on how effective learning could be when taken in the context of art to boostcreativity in children; and also enable the teacher to identify some activities that could or should be incorporated in the teaching of children. Since creativity is increasingly gaining recognition as ahuman characteristic that can be (and should be) developed through education, there is the need to make conscious efforts to develop children’s creativity and learning through art education. This way,teachers do not necessarily produce children who would by all means become artists but rather creative children who can transfer the skills they have learnt through art to other subject areas and in effect to all other facets of their lives.